ANALISIS PENGARUH FAKTOR INTERNAL (INTELEGENSI, MINAT, BAKAT, MOTIVASI, USIA) DAN FAKTOR EKSTERNAL (LINGKUNGAN, PENDIDIKAN, PENGALAMAN, PELATIHAN) TERHADAP PEMAHAMAN PEMBIAYAAN MUDHARABAH DAN MURABAHAH (STUDI PADA BMT DI KABUPATEN KEBUMEN) - Kusuma, Wati (P4M STIE Putra Bangsa, 2013)
This study was conducted at Baitul Maal Wa Tamwil (BMT) employee who join in BMT Association of Kebumen Regency. This study is entitled Ã¢â‚¬ËœThe Effect Analysis of Internal Factors (Intelligence, Interests, Talent, Motivation, Age) and External Factor (Environment, Education, Experience, Training) toward Understanding of Mudharaba and Murabahah